Applicability of the model of inclusive education in early childhood education: a case study - Nelis, Pille; Pedaste, Margus; Šuman, Carolina (Frontiers in Psychology, 2023)
Despite the development of policies and research supporting it, inclusion remains a challenge in contemporary education. We have developed a theoretical model for implementing inclusive education, thereby supporting early childhood education quality. It is necessary to establish the applicability of this model in order to apply it to improve the practices for adopting inclusive education. We conducted a case study, which showed that all levels and key characteristics of the theoretical model were also relevant in practice. However, as a result of the case study, the features describing the key characteristics were modified compared with the initial model. Additionally, the case study revealed that some of the features did not appear in practice. Those undetected features were mostly related to understanding the concept of inclusive education and the philosophy of inclusion. There appeared a need for a clearer understanding of inclusion on both the institutional and state level. The implementation of inclusive education does not in itself always increase inclusion or reduce exclusion. Therefore, when implementing inclusive education, it is necessary to think carefully about what is being done to allow all children to be meaningfully involved in the same classroom and by their teachers.